Optimized Ice Formulation Containing Tea Polyphenols and Phytic Acid and Its Effect on the Preservation of Pomfret - Xie Jing; Zhang Zhen; Li Liu; Yang Shengping (Zhileng xuebao)
Based on a study on the effects of a biological preservative on the quality of pomfret, ice formulation through a compound of biological preservatives was optimized using an orthogonal experimental design method involving two factors and three levels by assessing the quality indicators (sensory evaluation), microbial index (total viable counts (TVC) and aerobic plate counts (APC)), and physiochemical index (total volatile basic nitrogen (TVB-N), thiobarbituric acid value (TBA), and K value). According to the results, pomfret treated with ice containing 0.5% (w/v) tea polyphenols and 0.15% (v/v) phytic acid showed better indicators than the control group, and its shelf life can be extended from 11 ~ 12 days to 21 ~23 days under a temperature of 1 ℃.